Pemberdayaan Masjid di Indonesia dalam Perspektif Institutional Building - Dewi, Rita Sukma (Jurnal Ilmiah Administrasi Publik, 2019)
The development of the religious field is believed to be an alternative solution to the choices of development strategies. Assuming that religion always leads to goodness, the offer of development based on religious values is always interesting to explore. The mosque as a religious institution turned out to have the potential as a community empowerment institution. With the function embedded in it, the mosque is not only used for the sake of worship but also carries out several social functions such as education, culture and even the economy. Mosques has discoveredto be a social capital to improve the development of Indonesian society. The aims of this research is the first, to describe the elements of mosque empowerment as an institution. Second, to determined mosque empowerment efforts carried out by the government.